Rancang Bangun Website Pencatatan Penerima Bantuan di Desa Keramas - Ardana, I Made Putra Yudha; Putra, I Gede Juliana Eka; Utami, Nengah Widya (Universitas Multi Data Palembang, 2025)
The manual recording of social assistance recipients in Keramas Village has led to inefficiencies, including data inaccuracies, lengthy search processes, and difficulties in tracking data changes. Advances in information technology highlight the need for digital solutions to enhance data accuracy and processing speed. This study employs the Scrum methodology, implemented across three sprints, encompassing database design, user interface (UI) development, CRUD features, data search functionality, admin login system, data visualization using Chart.js, and PDF export capability. The system was developed using Laravel, Bootstrap, MySQL, and PHP technologies. The results demonstrate the successful development of a system featuring key functionalities: recording and managing BST/BLT recipient data, keyword-based data search, graphical data visualization, and PDF export capability. Blackbox testing confirmed that all system functions operate optimally without significant issues. The study concludes that the developed system effectively replaces manual recording methods, improves operational efficiency, and reduces error risks. For future development, recommendations include adding new features, expanding the scope of manageable social assistance programs, and enabling public access to enhance transparency. Keywords— Information System, Social Assistance, Website, Laravel, Scrum, Keramas Village